Contributions of ICTs towards Agricultural Development Among Agricultural Researchers in Ibadan North West Local Government, Oyo State, Nigeria - Oyewole, Oyetoro John; Ige , Adetunbi Saheed; Oyetunde, Oladipo Solomon (Asian Journal of Agriculture and Rural Development, 2013)
The study examines the contributions of Information and Communication Technology (ICT) towards Agricultural Development among Agricultural Researchers in Ibadan North West Local Government Area of Oyo State. Random sampling technique was used in the selection of 50 respondents that constitute the sample size for the study. Primary data were collected through the use of a well-structured questionnaire from the Agricultural researchers. Frequency counts, Percentages and Pearson Product Moment Correlation (PPMC) were used to analyse the data. Analysis of the data revealed collected that majority (70%) of the respondents are male, (64%) are married and (58%) had ICT usage experience of 1-5years. The result also shows that the mean age of the respondents is 36.5years while (62%) had Post Graduate degree education. There is a significant relationship between contributions of ICT facilities to agricultural development and selected agricultural websites accessed which are worldagriculture.com(r = 0.044, p= 0.002), moa.gov.jm (r = 0.364, p= 0.010), iita.org (r = 0.358, p= 0.012) and agweb.com (r = 0.435, p= 0.002). The study therefore recommends that internet facilities should be made available and affordable to agricultural researchers to enhance their accessibility, usage and contributions to agricultural development.